2017
DOI: 10.20937/atm.2017.30.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil heat storage and phase shift correction on energy balance closure of paddy fields

Abstract: RESUMENSe utilizó el método de covarianza eddy para medir los flujos de energía en un arrozal con ahorro de agua de riego en la Llanura del Sur de China, durante la etapa de crecimiento del arroz en 2013. También se analiza la respuesta del balance de energía superficial al cambio de almacenamiento térmico en el suelo entre las placas de flujo térmico enterradas a una profundidad específica y la superficie, y la corrección del desfase de los componentes del balance de energía, por medio de tres métodos estadís… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…As reported by different studies, the omission of the soil heat storage results in the underestimation of the energy EBC by up to 7 %. For instance, Liu et al (2017) reported an increase in OLS slope of an average 8.8 % and a mean daily EBR increase of 5 % when the soil heat storage term was considered in their study in the Taihu Lake region of the Southern China Plain. In their study in the three sites in the Badan Jaran desert, Li et al (2014) analysed the effect of including soil heat storage derived by different methods in the energy balance closure; their EBR improved by between 1.5 and 4 %.…”
Section: Day-night-time Effectsmentioning
confidence: 99%
“…As reported by different studies, the omission of the soil heat storage results in the underestimation of the energy EBC by up to 7 %. For instance, Liu et al (2017) reported an increase in OLS slope of an average 8.8 % and a mean daily EBR increase of 5 % when the soil heat storage term was considered in their study in the Taihu Lake region of the Southern China Plain. In their study in the three sites in the Badan Jaran desert, Li et al (2014) analysed the effect of including soil heat storage derived by different methods in the energy balance closure; their EBR improved by between 1.5 and 4 %.…”
Section: Day-night-time Effectsmentioning
confidence: 99%
“…Energy balance closure was evaluated via the energy balance ratio (EBR) method, which was calculated based on the cumulative available energy (Rn -G) and turbulent energy fluxes (LE + Hs) over specific time periods. Both hourly and daily EBR were improved by including the fluxes correction [11] compared with the results for original measurements (Figure 1), with an average increase of 14.5% and 12.8% for the hourly and daily scale, respectively. Yet, the energy fluxes measured by the EC system are not completely closed after the correction due to the energy balance deficit problem, although the mean daily EBR (0.93 and 0.85 in 2015 and 2016 rice seasons, respectively) of the EC measurement in the WSI rice fields was acceptable.…”
Section: Evaluation Of Energy Balance Closurementioning
confidence: 91%
“…The value of EF fluctuates greatly before sunset among observation days, as seen from the error bar in Figure 2. This was ascribed to the large temperature variation, unstable atmospheric turbulence, and advection exchange at sunset, and the inaccurate instantaneous fluxes measurement by the EC system [11]. In addition, the EF was occasionally greater than 1 during the transition periods in the morning or evening (at 7:00-8:00 and 15:00-16:00).…”
Section: Diurnal Variation Of Energy Budget Components and Evaporativmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of border plots effectively separated irrigation treatments. To induce slight drought and promote the penetration of roots of wheat, the irrigation quota was reduced at the over-winter and jointing stages, whereas more water was delivered at the critical flowering and filling stages [40,41]. The amount of full irrigation (I4) was calculated according to Equation (1), and detailed information of irrigation for different treatments was presented in Table 1.…”
Section: Experimental Designmentioning
confidence: 99%